High-pressure-resistant and low-dissolution filtering central tube and preparation method thereof

By using polyphenylene ether and other functional components in the filter center tube material to form a complex multivariate crosslinking network, the problem of insufficient pressure resistance and dissolution performance of existing materials is solved, and the combination of high pressure resistance and low dissolution performance is achieved, adapting to high pressure application scenarios and improving the stability of the material.

CN119662010AInactive Publication Date: 2025-03-21DELSTAR TECH SUZHOU
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510179440.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-19
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing filter center pipe materials have insufficient pressure resistance and dissolution performance, making it difficult to adapt to high pressure and strict application scenarios.

Method used

Polyphenylene ether (PPO) is used as the base material, combined with maleic anhydride grafted polyphenylene ether, cyclopentadiene grafted polystyrene, modified glass fiber and maleic anhydride grafted elastomer, a complex multivariate crosslinking network is formed through the Diels-Alder reaction and ester bonds, which improves the compressive strength of the material and reduces the dissolution performance.

Benefits of technology

The high pressure resistance and low dissolution properties of the material are achieved, adapting to higher pressure application scenarios. At the same time, through the reversibility of the Diels-Alder reaction, the material can flexibly absorb stress during impact, reducing fatigue and damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119662010A_ABST
    Figure CN119662010A_ABST
Patent Text Reader

Abstract

The invention provides a high-pressure-resistant and low-dissolution filtering central tube and a preparation method thereof. The high-pressure-resistant and low-dissolution filtering central tube comprises polyphenyl ether, maleic anhydride grafted polyphenyl ether, cyclopentadiene grafted polystyrene, a maleic anhydride grafted elastomer, modified glass fibers, a main antioxidant and an auxiliary antioxidant, the modified glass fiber is selected from aminated glass fiber, carboxylated glass fiber or hydroxylated glass fiber. According to the material disclosed by the invention, cyclopentadiene grafted polystyrene, maleic anhydride grafted polystyrene and maleic anhydride grafted elastomer are selected to form a ring-shaped cross-linked structure, and meanwhile, maleic anhydride and modified glass fibers are in ester bond connection, so that maleic anhydride, cyclopentadiene and modified glass fibers are used as association points of a cross-linked network; chemical cross-linking is established among different components, a complex multi-element cross-linked network is formed, the pressure resistance of the material can be improved, and dissolution can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pipes, and in particular to a high-pressure-resistant, low-dissolution filtering central pipe and a preparation method thereof. Background Art

[0002] As one of the important components of the spiral membrane element, the filter center tube is in direct contact with the clean water and plays a role in diversion. When the spiral membrane element is in operation, it needs to input different driving pressures, ranging from 1.0MPa for small household membrane elements to 5.5MPa for seawater desalination membrane elements. Some membrane elements for special applications (such as liquid concentration, garbage liquid treatment, etc.) require higher operating pressures, up to 8.0-16.0MPa.

[0003] At present, the materials of filter center tubes on the market are divided into metal and plastic. Metal materials involve food contact stainless steel, which has poor welding with filter materials and high costs, so they are seldom used. Plastic materials include PVC, ABS, PPO, PSU, etc. PVC materials are greatly affected by extrusion shear, have a narrow operating window, and the heat resistance of the product is poor. PSU materials have excellent performance, but the resin cost is high, and has high requirements for extrusion, and requires additional annealing processes. It is generally used in special scenarios, such as the pharmaceutical and semiconductor industries. ABS materials are relatively low in price and suitable for extrusion molding, but have poor pressure resistance. Due to the limitations of the synthesis process, ABS usually has average dissolution performance and is difficult to use in scenarios with high requirements for dissolution. PPO materials are moderately priced, and most of the modified PPOs available for extrusion processing on the market are modified PPOs, such as PPO / PS blended modified resins. The processing performance has been greatly improved, but the pressure resistance is difficult to adapt to the increasing number of high-requirement scenarios.

[0004] Therefore, it is necessary to develop a filter center tube material and product with higher pressure resistance and lower dissolution performance to adapt to more demanding application scenarios. Summary of the invention

[0005] In view of the shortcomings of the prior art mentioned above, the object of the present invention is to provide a high-pressure resistant, low-dissolution filter center tube to solve the problems of poor compressive strength and dissolution performance of the filter center tube material in the prior art. At the same time, the present invention will also provide a preparation method of the high-pressure resistant, low-dissolution filter center tube.

[0006] In order to achieve the above-mentioned object and other related objects, the present invention provides the following technical solutions: In a first aspect of the present invention, there is provided a high pressure resistant, low dissolution filtering central tube, comprising the following components in parts by weight: 10-35 parts by weight of polyphenylene ether (PPO); 10-30 parts by weight of maleic anhydride grafted polyphenylene ether (PPO-g-MAH); 10-40 parts by weight of cyclopentadiene grafted polystyrene; 5-15 parts by weight of maleic anhydride grafted elastomer; 10-30 parts by weight of modified glass fiber; 0.2-0.4 parts by weight of primary antioxidant; 0.1-0.3 parts by weight of a secondary antioxidant; Wherein, the modified glass fiber is selected from amino glass fiber, carboxyl glass fiber or hydroxylated glass fiber.

[0007] The filtering center tube of the present invention selects polyphenylene ether resin as the base material, uses polystyrene to improve the processability of the material, uses glass fiber to enhance the material strength, and uses elastomer to improve the toughness of the material. The present invention forms a complex multi-crosslinked network by grafting and modifying different components, using maleic anhydride, cyclopentadiene, and carboxyl (or amino, or hydroxyl) as the connection points of the crosslinked network, establishing chemical crosslinks between different components; wherein maleic anhydride and cyclopentadiene form a cyclic crosslinked structure through Diels-Alder reaction, and maleic anhydride forms an ester bond with carboxyl (or amino, or hydroxyl). The formation of the multi-crosslinked network can effectively transmit and disperse stress and improve the compressive strength of the material. The modification of the glass fiber enhances its connection strength with each polymer matrix and reduces the precipitation of the glass fiber. The glass fiber, as a unit of the crosslinked network, can be evenly dispersed to reduce the accumulation of the glass fiber.

[0008] In addition, due to the reversibility of the Diels-Alder reaction, when the filter center tube needs to reduce shock or absorb impact (such as under instantaneous pressure), the cyclic cross-linked structure between maleic anhydride and cyclopentadiene can temporarily dissociate, allowing the material to flexibly absorb impact and stress and reduce material fatigue or damage; when the pressure is eliminated, maleic anhydride and cyclopentadiene can re-react to form a stable ring structure and form cross-linking points again to ensure the mechanical strength and stability of the material.

[0009] Furthermore, the amino-treated glass fiber is prepared by the following method: immersing the pretreated glass fiber in an organic solution containing an aminosilane coupling agent, adding a small amount of deionized water, taking it out after soaking for a period of time and curing it, and obtaining the amino-treated glass fiber after washing and drying.

[0010] Wherein: the aminosilane coupling agent is selected from 3-aminopropyltrimethoxysilane (APTMS), 3-aminopropyltriethoxysilane (APTES), N-(2-aminoethyl)-3-aminopropyltrimethoxysilane (DAMO); The amount of the aminosilane coupling agent used accounts for 1%-3% of the mass of the organic solvent; The organic solvent is selected from ethanol or isopropanol; The amount of deionized water used accounts for 2%-5% of the volume of the organic solvent; The curing temperature is 100℃-120℃ and the curing time is 1-2h.

[0011] Furthermore, the carboxylated glass fiber is prepared by the following method: the pretreated glass fiber, carboxylic acid and activator are placed in an organic solvent, mixed evenly and heated to react for a period of time, and the glass fiber is taken out after the complete reaction, and the carboxylated glass fiber is obtained after cooling, washing and drying.

[0012] Wherein: the carboxylic acid is selected from succinic acid, citric acid or acrylic acid, and the amount of the carboxylic acid accounts for 2%-4% of the mass of the glass fiber; The activator is selected from triethylamine (TEA) or copper sulfate, and the amount of the activator is 1%-5% of the mass of the carboxylic acid; The organic solvent is selected from dimethylformamide (DMF) or dimethyl sulfoxide (DMSO); The heating reaction temperature is 50°C-60°C, and the reaction time is 1-3h.

[0013] Furthermore, the hydroxylated glass fiber is prepared by the following method: immersing the pretreated glass fiber in an alcohol solution containing a silane coupling agent, adding a small amount of a strong catalyst dropwise, heating and refluxing for a period of time, then taking out the glass fiber, cooling, washing, and drying to obtain the hydroxylated glass fiber.

[0014] Wherein: the strong catalyst is selected from tetrafluoroboric acid, and the amount of the tetrafluoroboric acid used accounts for 0.1%-1% of the volume of the alcohol solution; The alcohol solution is selected from methanol or isopropanol; The heating reflux reaction temperature is 100°C-120°C, and the reaction time is 0.5-1h.

[0015] Furthermore, the glass fiber is pretreated by the following method: the glass fiber is placed in acetone or ethanol, fully soaked to remove surface pollutants, and then immersed in a concentrated sulfuric acid / hydrogen peroxide mixture for a period of time after drying to fully expose the silanol groups on the surface of the glass fiber, and then washed and dried for use.

[0016] The pretreated glass fiber can more easily combine with amino, carboxyl or hydroxyl groups, and the connection strength is higher, thereby ensuring that maleic anhydride forms a stable chemical bond with the modified glass fiber surface, reducing glass fiber precipitation and dissolution.

[0017] Furthermore, the average length of the glass fiber is 1-10 mm, and the average diameter is 5-15 μm.

[0018] Further, the grafting rate of maleic anhydride in the maleic anhydride grafted polyphenylene ether is 1-2wt%. Among them, the content of maleic anhydride should not be too little, otherwise the compatibility with the resin matrix and the glass fiber will be reduced, and the crosslinking strength between cyclopentadiene and amino, hydroxyl or carboxyl groups will be reduced, so that the pressure resistance of the material is reduced and the solubility is deteriorated; the content of maleic anhydride should not be excessive, otherwise the viscosity of the material will increase, making it difficult to extrude and mold.

[0019] The maleic anhydride grafted polyphenylene ether is prepared by the following method: firstly dissolving maleic anhydride and an initiator in an organic solvent, then adding polyphenylene ether particles and extruding and melting in an extruder to obtain the maleic anhydride grafted polyphenylene ether.

[0020] Wherein, the initiator is selected from azobisisobutyronitrile (AIBN) or dicumyl peroxide (DCP); The amount of the initiator is 0.1%-0.5% of the mass of the polyphenylene ether; The organic solvent is selected from acetone, toluene or chloroform; The amount of the organic solvent is 3%-5% of the mass of the polyphenylene ether; The melting temperature is 240℃-280℃.

[0021] Further, the maleic anhydride grafted elastomer includes one or a combination of maleic anhydride grafted SEBS, maleic anhydride grafted EVA, maleic anhydride grafted ethylene propylene rubber, and maleic anhydride grafted POE; preferably maleic anhydride grafted SEBS. The addition of maleic anhydride grafted SEBS can not only form crosslinks with cyclopentadiene, because of its good compatibility with PPO, but also improve the compatibility of PS, glass fiber and PPO, and enhance the toughness of the material.

[0022] Furthermore, the grafting rate of maleic anhydride in the maleic anhydride grafted elastomer is 1.5-3wt%.

[0023] Furthermore, the grafting rate of cyclopentadiene in the cyclopentadiene-grafted polystyrene is 0.5-1.5wt%.

[0024] The cyclopentadiene grafted polystyrene is prepared by the following method: polystyrene, cyclopentadiene and an initiator are mixed in an organic solvent, a protective atmosphere is introduced, and the mixture is heated for a period of time for reaction. After the reaction is complete, the mixture is cooled, precipitated, washed and dried to obtain the cyclopentadiene grafted polystyrene.

[0025] Wherein: the initiator is selected from azobisisobutyronitrile (AIBN) or benzoyl peroxide (BPO); The amount of the initiator is 0.5%-1.5% of the mass of the polystyrene; The organic solvent is selected from toluene, xylene or chloroform; The heating reaction temperature is 80°C-100°C, and the reaction time is 4-6h.

[0026] Cyclopentadiene-grafted polystyrene has better compatibility with polyphenylene ether, which can improve the uniformity of the material and reduce dissolution; and due to the structural characteristics of cyclopentadiene, the thermal expansion coefficient of polystyrene can be reduced after grafting, thereby ensuring the structural stability of the filter center tube.

[0027] Furthermore, the mass ratio of the maleic anhydride grafted polyphenylene ether and the maleic anhydride grafted elastomer, the mass of the cyclopentadiene grafted polystyrene, and the mass of the modified glass fiber is 1: (0.6-1.5): (0.2-0.8).

[0028] Maleic anhydride and cyclopentadiene form a cyclic cross-linked structure through the Diels-Alder reaction. At the same time, maleic anhydride forms a cross-link with the carboxyl group (or amino group, or hydroxyl group) of the modified glass fiber. However, since maleic anhydride prefers to combine with cyclopentadiene, the amount of modified glass fiber and cyclopentadiene-grafted polystyrene should be balanced to ensure sufficient cross-linking of maleic anhydride with both, avoiding precipitation due to insufficient cross-linking of the modified glass fiber or dissolution due to insufficient cross-linking of the polystyrene.

[0029] Furthermore, the primary antioxidant is selected from AO 1010 (produced by BASF in China); and the secondary antioxidant is selected from AO 168 (produced by BASF in China).

[0030] The second aspect of the present invention provides a method for preparing a high pressure resistant, low dissolution filtering central tube, comprising the following steps: S1, preparing cyclopentadiene grafted polystyrene and modified glass fiber respectively for standby use; S2, weighing polyphenylene ether, maleic anhydride grafted polyphenylene ether, maleic anhydride grafted elastomer, cyclopentadiene grafted polystyrene, primary antioxidant and secondary antioxidant in proportion, putting them into a high-speed mixer and mixing them evenly to obtain a premix; S3, adding the premix obtained in step S2 into a twin-screw extruder, preheating for a period of time, and then feeding the modified glass fiber into the side feed, and melt-blending and extruding into a blank tube; S4. Further process the raw tube to obtain a filtering center tube.

[0031] Furthermore, in step S3, the preheating temperature is 160°C-200°C, and the preheating time is 5-20 minutes.

[0032] Furthermore, in step S3, the extrusion temperature is 180°C-280°C, and the screw speed is 200-600r / min.

[0033] During the preparation process, maleic anhydride and cyclopentadiene are first cross-linked through blending and preheating to form a six-membered ring structure to promote uniform dispersion between the polymers, and then modified glass fiber is added to connect the unreacted maleic anhydride with the modified glass fiber to promote uniform dispersion of the modified glass fiber, prevent agglomeration, and make the combination more stable, making it less likely for the glass fiber to precipitate.

[0034] As described above, the high-pressure resistant and low-dissolution filtering center tube and the preparation method thereof of the present invention have the following beneficial effects: the polystyrene grafted with cyclopentadiene prepared by the present invention has better compatibility with polyphenylene ether, elastomer and glass fiber. On the one hand, due to the structural characteristics of cyclopentadiene, the thermal expansion coefficient of polystyrene can be reduced after grafting, thereby ensuring the structural stability of the filtering center tube and improving its pressure resistance performance; On the other hand, cyclopentadiene and maleic anhydride form a cyclic cross-linked structure through the Diels-Alder reaction, and maleic anhydride forms an ester bond with the carboxyl group (or amino group, or hydroxyl group) of the modified glass fiber, thereby establishing chemical cross-links between different components with maleic anhydride, cyclopentadiene, and carboxyl group (or amino group, or hydroxyl group) as the connection points of the cross-linked network, forming a complex multi-element cross-linked network, which can effectively transfer and disperse stress and improve the compressive strength of the material; On the other hand, due to the reversibility of the Diels-Alder reaction, when the filter center tube needs to reduce shock or absorb impact, the cyclic cross-linked structure between maleic anhydride and cyclopentadiene can be temporarily dissociated, allowing the material to flexibly absorb impact and stress and reduce material fatigue or damage. When the pressure is eliminated, maleic anhydride and cyclopentadiene can react again to form a stable cyclic structure and form cross-linking points again, ensuring the mechanical strength and stability of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a photograph of the filtration center tube prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0036] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.

[0037] Example 1 Preparation of cyclopentadiene grafted polystyrene: In a reaction vessel, polystyrene is dissolved in a toluene solvent, and then cyclopentadiene and azobisisobutyronitrile are added to the mixed solution, nitrogen is introduced to remove oxygen in the reaction vessel, and then the closed reaction vessel is heated to 80°C for 6 hours. After the reaction is complete, the mixture is naturally cooled to room temperature, and then the mixture is poured into a large amount of cold methanol for precipitation, and the precipitate is washed with methanol for multiple times to remove unreacted cyclopentadiene and other impurities, and the precipitate is dried in a vacuum drying oven at low temperature until it is completely dried to obtain cyclopentadiene-grafted polystyrene. The mass ratio of polystyrene, cyclopentadiene and azobisisobutyronitrile is 98:1.2:0.8.

[0038] Preparation of carboxylated glass fiber: The glass fiber is placed in acetone and fully soaked to remove surface pollutants. After drying, the glass fiber is soaked in a concentrated sulfuric acid / hydrogen peroxide mixture for 12 hours to fully expose the silanol groups on the surface of the glass fiber, washed and dried to obtain the pretreated glass fiber; in a reaction container, succinic acid and triethylamine are added to a dimethylformamide solvent, mixed evenly, and the mixed solution is heated to 50°C, and then the pretreated glass fiber is soaked in the mixed solution for reaction for 2 hours. After the reaction is completed, the glass fiber is taken out of the solution, allowed to cool naturally at room temperature, and then washed and dried to obtain a carboxylated glass fiber. Among them, the mass ratio of glass fiber, succinic acid and triethylamine is 97:3:0.1.

[0039] A high pressure resistant, low dissolution filtering central tube, the preparation method of which comprises the following steps: S1. Weigh the cyclopentadiene grafted polystyrene and carboxylated glass fiber prepared above for later use; S2, weighing 30 parts by weight of polyphenylene ether, 25 parts by weight of maleic anhydride grafted polyphenylene ether, 5 parts by weight of maleic anhydride grafted SEBS, 25 parts by weight of cyclopentadiene grafted polystyrene, 0.3 parts by weight of primary antioxidant and 0.2 parts by weight of secondary antioxidant, putting them into a high-speed mixer and mixing them evenly to obtain a premix; S3, adding the premix obtained in step S2 into a twin-screw extruder, preheating at 180° C. for 15 min, then feeding 15 parts by weight of the carboxylated glass fiber prepared above into a side feed, melt blending at 280° C., and continuously extruding into a blank tube through a central tube die; S4. Further process the raw tube to obtain a filtering center tube.

[0040] Example 2 Preparation of amino glass fiber: The glass fiber is placed in acetone and fully soaked to remove surface pollutants. After drying, the glass fiber is soaked in a concentrated sulfuric acid / hydrogen peroxide mixture for 12 hours to fully expose the silanol groups on the surface of the glass fiber, washed and dried to obtain the pretreated glass fiber; 3-aminopropyltrimethoxysilane is diluted in ethanol at a ratio of 3%, and deionized water with a volume of 3% of ethanol is added, and the pretreated glass fiber is immersed in the aminosilane solution for 30 minutes, the soaked glass fiber is taken out, slightly air-dried, and then placed in an oven for curing at 100°C for 1 hour, and then washed with ethanol to remove unreacted silane coupling agent. The washed glass fiber is dried at low temperature in an oven to obtain amino glass fiber.

[0041] A high pressure resistant, low dissolution filtering central tube, the preparation method of which comprises the following steps: S1. Weigh the cyclopentadiene grafted polystyrene prepared in Example 1 and the amino glass fiber prepared above for later use; S2, weighing 30 parts by weight of polyphenylene ether, 25 parts by weight of maleic anhydride grafted polyphenylene ether, 5 parts by weight of maleic anhydride grafted SEBS, 25 parts by weight of cyclopentadiene grafted polystyrene, 0.3 parts by weight of primary antioxidant and 0.2 parts by weight of secondary antioxidant, putting them into a high-speed mixer and mixing them evenly to obtain a premix; S3, adding the premix obtained in step S2 into a twin-screw extruder, preheating at 180° C. for 15 min, then feeding 15 parts by weight of the amino glass fiber prepared above into the side feed, melt blending at 280° C., and continuously extruding through a central tube die to form a blank tube; S4. Further process the raw tube to obtain a filtering center tube.

[0042] Example 3 Preparation of hydroxylated glass fiber: The glass fiber is placed in acetone and fully soaked to remove surface pollutants. After drying, the glass fiber is soaked in a concentrated sulfuric acid / hydrogen peroxide mixture for 12 hours to fully expose the silanol groups on the surface of the glass fiber, washed and dried to obtain the pretreated glass fiber; epoxypropyltrimethoxysilane is diluted in methanol at a ratio of 3%, the glass fiber is soaked in the alcohol solution, and then 0.5% tetrafluoroboric acid by volume of the alcohol solution is added dropwise, heated to 120°C for reflux reaction for 1 hour, and the glass fiber is taken out after the reaction is complete, and rinsed with a large amount of deionized water to remove residual tetrafluoroboric acid and methanol, and dried in an oven at 80°C to obtain hydroxylated glass fiber.

[0043] A high pressure resistant, low dissolution filtering central tube, the preparation method of which comprises the following steps: S1. Weigh the cyclopentadiene grafted polystyrene prepared in Example 1 and the hydroxylated glass fiber prepared above for later use; S2, weighing 30 parts by weight of polyphenylene ether, 25 parts by weight of maleic anhydride grafted polyphenylene ether, 5 parts by weight of maleic anhydride grafted SEBS, 25 parts by weight of cyclopentadiene grafted polystyrene, 0.3 parts by weight of primary antioxidant and 0.2 parts by weight of secondary antioxidant, putting them into a high-speed mixer and mixing them evenly to obtain a premix; S3, adding the premix obtained in step S2 into a twin-screw extruder, preheating at 180° C. for 15 min, then feeding 15 parts by weight of the hydroxylated glass fiber prepared above into the side feed, melt blending at 280° C., and continuously extruding through a central tube die to form a blank tube; S4. Further process the raw tube to obtain a filtering center tube.

[0044] Example 4 A high pressure resistant, low dissolution filtering central tube, the preparation method of which comprises the following steps: S1. Weigh the cyclopentadiene-grafted polystyrene and carboxylated glass fiber prepared in Example 1 for later use; S2, weighing 30 parts by weight of polyphenylene ether, 10 parts by weight of maleic anhydride grafted polyphenylene ether, 5 parts by weight of maleic anhydride grafted SEBS, 40 parts by weight of cyclopentadiene grafted polystyrene, 0.3 parts by weight of primary antioxidant and 0.2 parts by weight of secondary antioxidant, putting them into a high-speed mixer and mixing them evenly to obtain a premix; S3, adding the premix obtained in step S2 into a twin-screw extruder, preheating at 180° C. for 15 min, and then feeding 15 parts by weight of the carboxylated glass fiber prepared in Example 1 into the side feed, melt blending at 280° C., and continuously extruding through a central tube die to form a blank tube; S4. Further process the raw tube to obtain a filtering center tube.

[0045] Example 5 A high pressure resistant, low dissolution filtering central tube, the preparation method of which comprises the following steps: S1. Weigh the cyclopentadiene-grafted polystyrene and carboxylated glass fiber prepared in Example 1 for later use; S2, weighing 30 parts by weight of polyphenylene ether, 25 parts by weight of maleic anhydride grafted polyphenylene ether, 5 parts by weight of maleic anhydride grafted SEBS, 25 parts by weight of cyclopentadiene grafted polystyrene, 0.3 parts by weight of primary antioxidant and 0.2 parts by weight of secondary antioxidant, putting them into a high-speed mixer and mixing them evenly to obtain a premix; S3, adding the premix obtained in step S2 into a twin-screw extruder, preheating at 180° C. for 15 min, then feeding 30 parts by weight of the carboxylated glass fiber prepared in Example 1 into the side feed, melt blending at 280° C., and continuously extruding through a central tube die to form a blank tube; S4. Further process the raw tube to obtain a filtering center tube.

[0046] Comparative Example 1 A filtering central tube, the preparation method of which comprises the following steps: S1, weighing 55 parts by weight of polyphenylene ether, 5 parts by weight of SEBS, 25 parts by weight of polystyrene, 0.3 parts by weight of a primary antioxidant and 0.2 parts by weight of a secondary antioxidant, putting them into a high-speed mixer and mixing them evenly to obtain a premix; S2, adding the premix obtained in step S2 into a twin-screw extruder, preheating at 180° C. for 15 min, then feeding 15 parts by weight of unmodified glass fiber into the side feed, melt blending at 280° C., and continuously extruding through a central tube die to form a blank tube; S3. Further process the raw tube to obtain a filtering center tube.

[0047] Comparative Example 2 A filtering central tube, the preparation method of which comprises the following steps: S1, weighing 55 parts by weight of maleic anhydride grafted polyphenylene ether, 5 parts by weight of maleic anhydride grafted SEBS, 25 parts by weight of polystyrene, 0.3 parts by weight of primary antioxidant and 0.2 parts by weight of secondary antioxidant, putting them into a high-speed mixer and mixing them evenly to obtain a premix; S2, adding the premix obtained in step S2 into a twin-screw extruder, preheating at 180° C. for 15 min, then feeding 15 parts by weight of unmodified glass fiber into the side feed, melt blending at 280° C., and continuously extruding through a central tube die to form a blank tube; S3. Further process the raw tube to obtain a filtering center tube.

[0048] Performance Testing The filter center tubes prepared in Examples 1-5 and Comparative Examples 1-2 were placed in an environment of 23°C and 50% RH for 48 hours and then tested. The test results are shown in Table 1. Pressure resistance test, refer to the test standard GB / T 1041-2008 Determination of compression properties of plastics; Test method: Take a 100mm long sample tube with a wall thickness of 6mm (outer diameter 38mm / inner diameter 26mm) and place it horizontally on the test platform, press down at a uniform speed of 3mm / min, and test the maximum force when the tube undergoes compression deformation.

[0049] For the dissolution test, refer to Appendix A of "Sanitary Evaluation Standards for Drinking Water Distribution Equipment and Its Protective Materials" (2001). Test method: Prepare immersion water, cut the sample tube and place it at 1 cm. 2 The sample was immersed in 10 mL of immersion solution and immersed in light at 25 °C for 24 h before the dissolution-related properties were determined. The specific test method refers to GB / T 5750-2023 Standard Test Method for Drinking Water.

[0050] Total dissolved solids (TDS) are determined by weighing: the water sample is filtered and then dried at 180°C to obtain the weight of the solid residue.

[0051] The chloroform content was determined by gas chromatography-mass spectrometry (GC-MS).

[0052] Total organic carbon TOC, using an organic carbon analyzer.

[0053] Table 1 Performance test results of the filtration center tube of Examples 1-5 and Comparative Examples 1-2

[0054] According to the test results, cross-linking is formed between cyclopentadiene-grafted polystyrene and maleic anhydride-grafted polystyrene and maleic anhydride-grafted elastomer, and at the same time, cross-linking is formed between maleic anhydride-grafted polystyrene and maleic anhydride-grafted elastomer and modified glass fiber, which reduces the dissolution of components and can effectively transfer and disperse stress when impacted, thereby improving the compressive strength of the material. Among them, the combination of carboxylated glass fiber and maleic anhydride is more stable, making the cross-linking density of the material better and the various properties of the material better.

[0055] According to the comparison between Example 1 and Examples 4 and 5, maleic anhydride is more inclined to combine with cyclopentadiene, so the amount of modified glass fiber and cyclopentadiene-grafted polystyrene should be balanced to ensure sufficient crosslinking of maleic anhydride with both and avoid precipitation due to uncrosslinked modified glass fiber.

[0056] In summary, the material of the present invention uses cyclopentadiene grafted polystyrene and maleic anhydride grafted polystyrene and maleic anhydride grafted elastomer to form a ring-shaped cross-linked structure, and maleic anhydride is ester-bonded with modified glass fiber, so that maleic anhydride, cyclopentadiene and modified glass fiber are used as the connection points of the cross-linked network, chemical cross-linking is established between different components, and a complex multi-element cross-linked network is formed, which can improve the pressure resistance of the material and reduce dissolution. Therefore, the present invention effectively overcomes various shortcomings in the prior art and has a high industrial utilization value.

[0057] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A high pressure resistant, low dissolution filtering center tube, characterized in that: The composition comprises the following components in parts by weight: 10-35 parts by weight of polyphenylene ether; 10-30 parts by weight of maleic anhydride grafted polyphenylene ether; 10-40 parts by weight of cyclopentadiene grafted polystyrene; 5-15 parts by weight of maleic anhydride grafted elastomer; 10-30 parts by weight of modified glass fiber; 0.2-0.4 parts by weight of primary antioxidant; 0.1-0.3 parts by weight of a secondary antioxidant; Wherein, the modified glass fiber is selected from amino glass fiber, carboxyl glass fiber or hydroxylated glass fiber.

2. The high pressure resistant, low dissolution filtering central tube according to claim 1, characterized in that: The amino-treated glass fiber is prepared by the following method: immersing the pretreated glass fiber in an organic solution containing an aminosilane coupling agent, adding a small amount of deionized water, taking it out after immersion for a period of time and curing it, and obtaining the amino-treated glass fiber after washing and drying.

3. The high pressure resistant, low dissolution filtering central tube according to claim 2, characterized in that: The aminosilane coupling agent is selected from 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane; the amount of the aminosilane coupling agent is 1%-3% of the mass of the organic solvent.

4. The high pressure resistant, low dissolution filtering central tube according to claim 1, characterized in that: The carboxylated glass fiber is prepared by the following method: pretreated glass fiber, carboxylic acid and activator are placed in an organic solvent, mixed evenly and heated for a period of time, and after complete reaction, the glass fiber is taken out, cooled, washed and dried to obtain the carboxylated glass fiber.

5. The high pressure resistant and low dissolution filtering central tube according to claim 1, characterized in that: The hydroxylated glass fiber is prepared by the following method: immersing the pretreated glass fiber in an alcohol solution containing a silane coupling agent, adding a small amount of a strong catalyst dropwise, heating and refluxing for a period of time, then taking out the glass fiber, cooling, washing and drying, and obtaining the hydroxylated glass fiber.

6. The high pressure resistant, low dissolution filtering central tube according to claim 1, characterized in that: The cyclopentadiene grafted polystyrene is prepared by the following method: polystyrene, cyclopentadiene and an initiator are mixed in an organic solvent, a protective atmosphere is introduced, and the mixture is heated for a period of time for reaction. After the reaction is complete, the mixture is cooled, precipitated, washed and dried to obtain the cyclopentadiene grafted polystyrene.

7. The high pressure resistant, low dissolution filtering central tube according to claim 6, characterized in that: The initiator is selected from azobisisobutyronitrile or benzoyl peroxide; the amount of the initiator is 0.5%-1.5% of the mass of the polystyrene.

8. The high pressure resistant, low dissolution filtering central tube according to claim 1, characterized in that: The maleic anhydride grafted elastomer includes one or a combination of maleic anhydride grafted SEBS, maleic anhydride grafted EVA, maleic anhydride grafted ethylene propylene rubber, and maleic anhydride grafted POE.

9. The high pressure resistant and low dissolution filtering central tube according to claim 1, characterized in that: The mass ratio of the maleic anhydride grafted polyphenylene ether and the maleic anhydride grafted elastomer, the mass of the cyclopentadiene grafted polystyrene, and the mass of the modified glass fiber is 1: (0.6-1.5): (0.2-0.8).

10. A method for preparing a high pressure resistant, low dissolution filtering central tube as claimed in any one of claims 1 to 9, characterized in that: The steps include: S1, preparing cyclopentadiene grafted polystyrene and modified glass fiber respectively for standby use; S2, weighing polyphenylene ether, maleic anhydride grafted polyphenylene ether, maleic anhydride grafted elastomer, cyclopentadiene grafted polystyrene, primary antioxidant and secondary antioxidant in proportion, putting them into a high-speed mixer and mixing them evenly to obtain a premix; S3, adding the premix obtained in step S2 into a twin-screw extruder, preheating for a period of time, and then feeding the modified glass fiber into the side feed, and melt-blending and extruding into a blank tube; S4. Further process the raw tube to obtain a filtering center tube.

Citation Information

Patent Citations

  • Resin reinforcing fiberglass and thermoplastic resin composition

    CN111518294A

  • Dynamic bond cross-linked high-filling heat-conducting composite material as well as preparation method and application thereof

    CN113248900A

  • Resin composition, method for producing same, molded article, machine component, and

    CN114502653A

  • Resin composition, molded product, and plumbing mechanical component

    US20180079902A1

  • Poly(phenylene sulfide) resin composition, production method therefor, and molded article

    US20190270886A1